الأوراق التجارية الإلكترونية - منزول, يمينة (Ibn Khaldun University of Tiaret, 2024)
يعد موضوع الأوراق التجارية الإلكترونية من المواضيع القديمة الحديثة بتطورها من حيث آليات معالجتها وإنشائها والوفاء بها إلكترونيا، لذلك لا يمكن ا عتبارها من ضمن وسائل الوفاء الحديثة في المجال التجاري والمصرفي، وإنما طورت بتطور تقنيات الكتابة والتوقيع، وطورت كذلك إستجابة لمحاكاة الرقمنة مختلف القطاعات التجارية والمصرفية. لذا تهدف دراسة موضوع الأوراق التجارية الإلكترونية إلى الوقوف عن مدى استجابة التشريعات الدولية والوطنية لمتطلبات الرقمنة، ووضع تنظيم قانوني تبرز من خلاله الخصوصية الإلكترونية في الأوراق التجارية من جهة، دون المساس بالوظائف الأساسية أو المبادئ التي يرتكز عليها قانون الصرف وإمكانية توافق أحكام قانون الصرف التقليدية مع رقمنة الأوراق التجارية وقابليتها للتطبيق عليها من جهة أخرى مع إلزامية البحث عن الأطر الحمائية التشريعية المنتهجة للأوراق التجارية الإلكترونية، دوليا ووطنيا مدنيا وفنيا وجنائيا بما يكفل التعامل ا لآمن بها The subject of electronic commercial papers is considered one of the old and modern topics in terms of its development in terms of mechanisms for processing creating, and fulfilling it electronically. Therefore, it cannot be considered among the modern means of fulfillment in the banking field. Rather, it was developed with the development of writing and signing techniques, and it was also developed in response to the simulation of digitization in various commercial and banking sectors. Therefore, the study of the issue of electronic commercial papers aims to determine the extent to which international and national legislation responds to the requirements of digitization, and to develop a legal regulation through which electronic privacy in commercial papers is highlighted on the one hand, without prejudice to the basic functions or principles on which the exchange law is based and the possibility of compatibility of the provisions of the traditional exchange law with The digitization of commercial papers and their applicability to them, on the other hand, along with the obligation to search for the legislative protective policy adopted for electronic commercial papers, internationally and nationally civilly, technically, and criminally, in a way that ensures safe dealing with them.

التضامن الصرفي في الأوراق التجارية - قلتة, محمد الأمين; بن شاعة, براهيم (Ibn Khaldun University of Tiaret, 2024)
يعد التضامن مبدأ من مبادئ القانون التجاري، وأحد أهم الضمانات التي يعتمدها قانون الصرف من أجل حصول حامل الورقة التجارية على قيمتها عند ميعاد استحقاقها، إذ يحق لهذا الأخير الرجوع على أي موقع أو على جميع الموقعين بكامل قيمة الورقة التجارية. تعد الأ وراق التجارية من وسائل الدفع التي تقوم مقام النقود في الوفاء، فهي تؤدي نفس الوظيفة التي تؤديها النقود، كما وأنها قابلة للتداول، ونظرا لأهمية هذه الأوراق في المعاملات التجارية ولكي تقوم فعلا مقام النقود في الوفاء فقد أحاطها المشرع الجزائري بمجموعة من الضمانات حماية للثقة والائتمان القائم بين التجار،ويعتبر التضامن الصرفي من أهم هذه الضمانات؛ إذ يحمي حامل الورقة التجارية ويشعره بالأمان والطمأنينة، والذي يجعل كل موقع عليها ضامنا للوفاء عند امتناع المسحوب عليه وبذلك يمكن للحامل الرجوع على الملتزمين الصرفيين منفردين أو مجتمعين والمطالبة بقيمة الورقة التجارية سواء كان ذلك في ميعاد استحقاقها أم قبل ذلك الميعاد، فكل موقع عليها يكون مسؤولا على وجه التضامن مع الملتزمين الآخرين Solidarity is one of the principles of commercial law, and one of the most important guarantees adopted by the exchange law in order for the holder of the commercial paper to obtain its value when it is due, as the latter has the right to recourse to any signatory or to all signatories for the full value of the commercial paper. Commercial papers are considered a means of payment that takes the place of money in fulfillment. They perform the same function that money performs, and they are also negotiable. Given the importance of these papers in commercial transactions, and in order for them to actually take the place of money in fulfillment, the Algerian legislator has surrounded them with a set of guarantees to protect trust and credit. existing between merchants, and exchange solidarity is considered one of the most important of these guarantees. It protects the holder of the commercial paper and makes him feel safe and reassured, which makes every signatory of it a guarantor of payment in the event of the drawee’s refusal. Thus, the holder can return to the exchange obligors individually or jointly and claim the value of the commercial paper, whether that is on its maturity date or before that date. Each signatory of it is responsible. In solidarity with other committed people.
Accepted: 2025-01-26T13:11:52Z

الصفقات العمومية التي يبرمها أشخاص القانون الخاص في التشريع الجزائري مقارنا - كوثر, بن ملوكة (Université d'Oran 2 Mohamed Ben Ahmed, 2024)
الملخص يحظى مجال الصفقات العمومية بأهمية بالغة بالنسبة للاقتصاد الوطني، وتعود هذه الأهمية لاعتبار الصفقة العمومية الطريق القانوني الذي تستخدمه الدولة ومختلف المتعاملين من أجل انجاز المشاريع بجودة عالية بأقل التكاليف وآجال مدروسة، وكون تمويل الصفقات العمومية يعود للخزينة العامة للدولة وجب توفير الحماية القانونية لهذه العملية عن طريق إيجاد تنظيم قانوني خاص بها يحقق المصلحة العامة ويحترم الحرية الاقتصادية في ذات الوقت، وهو ما جسده المشرع الجزائري عمليا بإصدار المرسوم الرئاسي 15-247 الذي عرف عدة تعديلات سابقة ومواكبة لمتطلبات كل مرحلة، فالقول بالصفقة العمومية يحيل بالضرورة إلى أشخاص القانون العام أي الدولة والمؤسسات التابعة لها والقول بغير ذلك نوع من التضاد. لكن المشرع ألزم أشخاص القانون الخاص الخاضعين للتشريع التجاري بتطبيق أحكام التنظيم الصفقات العمومية في حالات محددة وهي التمويل الكلي أو الجزئي للصفقة من الخزينة العمومية (الدولة أو الجماعات الإقليمية) ما يخلق اشكال أي قانون يطبق في حالة النزاع وبالنتيجة أي هرم قضائي هو المختص في البت في منازعة أحد أطرافها أشخاص القانون الخاص ،وكذا حالات التمويل وتجسيدها عمليا، اضافة إلى دور الوسائل الودية المنصوص عليها في كل من تنظيم الصفقات العمومية أو قانون الإجراءات المدنية في حل المنازعات وتجسيد المشاريع واقعيا. Résumé Le domaine des marchés publics occupe une grande place dans l’économie nationale ; cela est dû au fait qu’un marché public est considéré comme la voie légale utilisée par l’État et les différents partenaires pour réaliser des projets au moindre coût et dans des délais raisonnés. Comme le financement des marchés publics relève du Trésor public, l’état est tenu d’assurer la protection juridique de ce processus en créant sa propre organisation juridique dans l’intérêt public tout en respectant la liberté économique, c’est ce que le législateur algérien a matérialisé, dans la pratique, par la promulgation du décret présidentiel n°15-274 qui a connu plusieurs modifications aux fins de de répondre aux exigences de chaque étape. Dire « Marché Public » renvoie nécessairement aux entités du droit commun, à savoir, l’état et ses institutions et affirmer les choses autrement serait une forme de contradiction. Toutefois, le législateur a engagé les entités du droit privé soumis à la législation commerciale dans l’application des dispositions de la réglementation des marchés publics dans un cas spécifique, à savoir, le financement total ou partiel du marché à partir du trésor public (États et/ou collectivités territoriales) ; de cela est issue une loi applicable en cas de conflit, avec pour conséquence, toute pyramide judiciaire compétente pour statuer sur un litige relevant en partie du droit privé, dans les cas de leur financement et matérialisation pratique, ainsi que lorsqu’il s’agit du rôle des moyens de règlement à l’amiable prévus aussi bien par la réglementation des marchés publics que par le Code de procédure civile dans la résolution des litiges et la réalisation concrète des projets. Abstract The field of public procurement occupies a major place in the national economy; this is due to the fact that a public procurement is considered to be the legal way used by the State and the various partners to carry out projects at the lowest cost and within reasonable deadlines. As the financing of public procurement is the responsibility of the Treasury, the State is required to ensure the legal protection of this process by creating its own legal organization in the public interest while respecting economic freedom, this is what the Algerian legislator materialized, in practice, by the promulgation of presidential decree No. 15-274 which has undergone several modifications in order to meet the requirements of each stage. To say "Public Procurement" necessarily refers to the entities of common law, namely, the state and its institutions and to affirm things otherwise would be a form of contradiction. However, the legislator has committed the private law entities subject to commercial law to apply the provisions of the public procurement regulation in a specific case, namely, the total or partial financing of the contract from the public treasury (States and/or territorial authorities); from this comes a law applicable in case of conflict, with the consequence, any judicial pyramid competent to rule on a dispute falling partly under private law, in cases of their financing and practical materialization, and when it concerns the role of the means of amicable settlement provided for by the regulation of public contracts as well as by the Code of Civil Procedure in the resolution of disputes and the concrete implementation of projects.
Keywords: Commercial and public company; Conflict of judicial compétences; Conflit des compétences judiciaires; Entreprise publique Industrielle; Entreprise publique commerciale; Financement par le trésor; Financing by treasury; Industrial public company; Marché; Market; Means of amicable settlement; Moyens de règlement à l’amiable